A clínica psicológica e a experiência da espiritualidade de pacientes em cuidados paliativos - Medeiros, Waleska de Carvalho Marroquim (2012)
With the advancement of scientific technological resources of medicine, life expectancy has increased substantially in recent decades. Diseases that were once fatal are now treatable. Diseases that had no prospect of cure had changed its course and development ensuring an increase in patient survival. The search for the extension and maintenance of life over time, it was shaping up as efforts of distancing and denial of death, sometimes through obstinate and futile treatments. The expansion of the quantity of life has come to occupy a privileged place on the tour. Given the increase in critically ill patients or out of therapeutic possibilities, the struggles of the scientific community about the quality of life turn to the need to integrate other dimensions of patient care inserted in palliative care programs, and focus strictly physical and biomedical. In this sense, spirituality has been identified as an important aspect of existential dimension, causing great impacts on physical health, especially in patients at the end of life. This work aims to understand the psychological clinic and experience the spirituality of patients enrolled in palliative care program at a public hospital in Recife through qualitative research, purposeful sampling clipping due to the specific theme. Sought to present the principles of palliative care by pointing the management of the health team to the patient without therapeutic possibility of cure; identify the comments made by the practice of psychology and the psychological experience of spirituality; present contributions that enable reflection in the comprehensive care offered to patients seriously patient, in order to offer a better quality of life